Approximation of IMSE-optimal Designs via Quadrature Rules and Spectral Decomposition. Issue 5 (27th May 2016) - Gauthier, Bertrand; Pronzato, Luc
Abstract : We address the problem of computing integrated mean-squared error (IMSE) optimal designs for interpolation of random fields with known mean and covariance. We assume that the mean squared error is integrated through a discrete measure and restrict the design space to its support. We show that the IMSE and its approximation by spectral truncation can be easily evaluated, which makes their global minimization affordable. Numerical experiments are carried out that illustrate the effectiveness of the approach.